INCREASED IPS LEARNING OUTCOMES THROUGH MAKE A MATCH LEARNING MODEL ON GRADE IV ELEMENTARY SCHOOL INPRES PERUMNAS ANTANG II MAKASSAR - Tenri Ampa, Andi (International Conference on Cultural Studies, 2018)
This study is an effort to improve IPS learning outcomes through the application of make a match learning model. The formulation of the problem in this research is how to improve the learning outcomes of IPS through the learning model make a match in the fourth grade students of Inpres Perumnas Antang II Makassar? The purpose of this study is to find out the results of IPS learning through make a match learning model in the fourth grade students of Inpres Perumnas Antang II Makassar. The type of research is classroom action research in the form of a cycle that is cycle I if the achievement of KKM standard has not been successful then continued in cycle II. The subjects of the study were the fourth grade students of SD Inpres Perumnas Antang II Makassar as many as 21 students. Data collection using observation, test, and documentation techniques while the data were analyzed descriptively qualitatively by describing the learning process of each cycle. The results showed that there was an increase of learning outcomes from cycle I to cycle II through the application of make a match learning model. In the first cycle is in the category is good enough because the teacher has not implemented the learning steps through the implementation of make a match learning model well while the learning cycle II is in the good category. The conclusion of this research is that the application of make a match can improve the learning result of IPS of fourth grade students of SD Inpres Perumnas Antang II Makassar.